Emergency remote teaching and the medical student - Maldonado, Karina; Maldonado, Luis Fernando Dzul (Technium Social Sciences Journal, 2022)
In the midst of the Covid-19 pandemic, the teacher transformed classroom education, guaranteeing access to transformational cognitive learning, migrating from classroom teaching to confinement teaching, called emergency remote teaching. Adapting has generated hard collaborative work with open education resources, implemented by the teacher. Objective. To evaluate the emergency remote teaching implemented in the education of medical students during the contingency period. Results. There are 3 spheres in emergency remote teaching: Digital Resources (Learning Activities) with 87% satisfaction, Educational Intermodality 47% (interaction of educational modalities) and Evaluation Criteria 32%. Conclusion. The digital resources and the evaluation criteria depend on the teaching commitment in each Learning Unit. Educational intermodality is based on the digital ability of the teacher, being important to implement training alternatives in them and therefore motivate the student to continue in the educational process.